IDENTIFIKASI SEKTOR EKONOMI UNGGULAN DAN KETIMPANGAN PENDAPATAN ANTAR KABUPATEN DI SUB DAS BENGAWAN SOLO HULU - S Andy Cahyono; Wahyu Wisnu Wijaya (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
The purposes of this study are: (1) to identify leading economic sectors and (2) to analyse income disparity among regencies in Upper Bengawan Solo sub watershed. The study covers 5 regencies: Wonogiri, Boyolali, Klaten, Sragen and Karanganyar. Data were analyzed using a Klassen typology to determine pattern and economy structure, Location Quotient (LQ) to identify leading economic sectors, Williamson Index to determine economic disparity and sectoral contribution to determine role of sector. The results show that leading economic sectors were different for each regency, i.e.Wonogiri (transport and communications), Karanganyar (processing industry), Boyolali (finance, real estate, and business services), Sragen (agriculture, livestock, forestry, and fisheries), and Klaten (construction). The leading sectors identified in each regency varied depending on the endowment of resources and comparative advantage. Based on their pattern and economy structure, Karanganyar can be categorized as advanced and fast growing region but Wonogiri as disadvantaged regions. The results also show that the income disparity among regencies was low (0.25) and tended to increase. The development policy of high economic growth with low disparity can be inclusively done by developing the leading sectors and paying attention to the economic transformation that occurred in each regency.